The Role of Children’s Literacy In Shaping Local Cultural Identity in The Era of Globalization - Budiyono, Apri Eka; Husni, M. (International Journal of Language and Culture, 2023)
In the rapidly evolving era of globalization, children in Indonesia face significant challenges in preserving their local cultural identity. Several factors contribute to this, including low interest in literature based on local culture and the strong influence of global culture, which dominates children’s media and education. Local culture-based literacy is a solution to strengthen children’s cultural awareness and local identity. This study aims to analyze the role of local culture-based literacy in shaping children’s cultural identity amidst globalization. Additionally, it seeks to identify the challenges in implementing such literacy and explore potential solutions. The research method used is a literature review, collecting relevant scholarly articles on local culture-based literacy and children’s cultural identity. This study examines existing research findings to identify factors influencing the effectiveness of cultural literacy in strengthening children’s cultural identity in the globalization era. The results indicate that local culture-based literacy positively shapes children’s cultural identity. This literacy enhances pride in local culture, despite challenges such as low reading interest in culturally-based materials, limited access, and the influence of global culture, which remain significant obstacles. Furthermore, the use of technology and educator training can serve as solutions to address these challenges.